A contribution to the development of the concept of nc flexible production systems for rotational parts machining - Rekecki, Jožef; Gatalo, Ratko; Hodolič, Janko; Borojoev, Ljubomir; Zeljković, Milan (Journal of Production Engineering, 1984)
In the paper are presented some results of developing the bases for defining the concept of NC flexible production systems and the bases for defining the characteristics of the elements in the WC flexible production system for rotational parts machining. Particularly, a rough concept of the entire system is given as well as the concept of integral connections of technological process design and appropriate control information with the control for the elements of flexible production system.